Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1176/appi.neuropsych.13010013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anticraving Efficacy of Right and Left Repetitive Transcranial Magnetic Stimulation in Alcohol Dependence: A Randomized Double-Blind Study

Abstract: The objective of this study was to compare the anticraving efficacy of high-frequency repetitive transcranial magnetic stimulation (rTMS) of the right versus left dorsolateral prefrontal cortex (DLPFC) in patients with alcohol dependence. Twenty patients with alcohol dependence syndrome were randomly allocated to receive either right or left rTMS over the right DLPFC (10 sessions at 10 Hz frequency; 20 trains per session; 4.9 seconds per train and intertrain interval 30 seconds) and were assessed on the Alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 31 publications
2
44
0
4
Order By: Relevance
“…Previous studies indicate high-frequency rTMS over the left DLPFC has a positive effect on cognition [3]. rTMS has also been reported to have anti-craving efficacy in various substance abuse disorders including alcohol dependence [489]. The patients with alcohol dependence have been displayed increased activity in the mesolimbic dopaminergic pathway, and the application of rTMS over the DLPFC is thought to have reduced craving by modulating the altered activity in the mesolimbic pathway through the meso-frontolimbic connections [489].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies indicate high-frequency rTMS over the left DLPFC has a positive effect on cognition [3]. rTMS has also been reported to have anti-craving efficacy in various substance abuse disorders including alcohol dependence [489]. The patients with alcohol dependence have been displayed increased activity in the mesolimbic dopaminergic pathway, and the application of rTMS over the DLPFC is thought to have reduced craving by modulating the altered activity in the mesolimbic pathway through the meso-frontolimbic connections [489].…”
Section: Discussionmentioning
confidence: 99%
“…rTMS has also been reported to have anti-craving efficacy in various substance abuse disorders including alcohol dependence [489]. The patients with alcohol dependence have been displayed increased activity in the mesolimbic dopaminergic pathway, and the application of rTMS over the DLPFC is thought to have reduced craving by modulating the altered activity in the mesolimbic pathway through the meso-frontolimbic connections [489]. It was demonstrated that high-frequency rTMS over the right DLPFC has a positive effect on decreasing craving score in patients with alcohol dependence and it is presumed to be due to transsynaptic suppression of the left DLPFC via transcallosal connections [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeting to the other hemisphere, the right DLPFC, with rTMS can also alleviate symptoms in depression [32], substance use disorders [33], posttraumatic stress disorders [4], and panic disorders [34]. Although the left PFC seems more vulnerable to high level of cortisol, the right PFC is also involved [35].…”
Section: Modulation Of Brain Activitymentioning
confidence: 99%